2016
DOI: 10.1007/s00198-016-3609-4
|View full text |Cite
|
Sign up to set email alerts
|

Clinical cone beam computed tomography compared to high-resolution peripheral computed tomography in the assessment of distal radius bone

Abstract: Clinical CBCT devices are able to analyze large portions of distal bones with good spatial resolution and limited irradiation. However, compared to dedicated HR-pQCT, the assessment of microarchitecture by NewTom 5G dental CBCT showed some discrepancies, for density measurements mainly. Further technical developments are required to reach optimal assessment of bone characteristics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
25
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 41 publications
2
25
0
Order By: Relevance
“…De Charry and colleagues have shown that CBCT correlated well with XTremeCT-I in the quantification of microstructural parameters of the cortical and trabecular bone at the distal radius. (8) Reported correlations are comparable to those in the present study. The present study extended these analyses by including the quantification of agreement relative to XtremeCT-II and by quantifying the accuracy relative to micro-CT.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…De Charry and colleagues have shown that CBCT correlated well with XTremeCT-I in the quantification of microstructural parameters of the cortical and trabecular bone at the distal radius. (8) Reported correlations are comparable to those in the present study. The present study extended these analyses by including the quantification of agreement relative to XtremeCT-II and by quantifying the accuracy relative to micro-CT.…”
Section: Discussionsupporting
confidence: 89%
“…De Charry and colleagues have shown that CBCT correlated well with XTremeCT‐I in the quantification of microstructural parameters of the cortical and trabecular bone at the distal radius . Reported correlations are comparable to those in the present study.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…Also, this recent investigation was done on a smaller FOV of 6 cm × 6 cm, for which an extrapolation of the effective dose can be calculated: Assuming the distance between X‐ray source and detector is constant and considering the scan length ratio, the extrapolated effective dose would be 10.7 μSv. Another group reported an effective dose of 10 μSv for a similar acquisition protocol with the same CBCT device …”
Section: Technical Specifications For a Customized Scan Of 6 CM On Hrmentioning
confidence: 99%